Potential protein hydrolysates from the white and purple flower varieties of Orthosiphon aristatus leaves - Chua, Lee Suan; Abdullah, Farah Izana; Lim, Teck Kwang; Lin, Qingsong (Elsevier, 2024)
This study was aimed to extract bioactive peptides from the white and purple flower varieties of Orthosiphon aristatus leaves. The herb is well known for its pharmacological importance, possibly attributed to its plant proteins. Phenol based extraction was used to extract plant proteins, and then hydrolysed by proteolytic enzymes such as trypsin (serine protease) and pepsin (aspartic protease). MS/MS analysis revealed that 145 and 125 proteins were detected from the white and purple flower varieties, respectively. Trypsin hydrolysates were showed to have a higher degree of hydrolysis (24–33%), resulting in higher antioxidant and antibacterial activities. The white flower of trypsin hydrolysates showed a higher radical scavenging activity which could be attributed to its higher content of stress proteins (19%). However, trypsin hydrolysates from the purple flower showed higher ferric reducing power and bacterial growth inhibition. The performance of hydrolysates was better than ampicillin in inhibiting Acinetobacter baumanni and Staphylococcus aureus.